ORGANOLEPTIC AND PHYSICAL QUALITY OF BROILER MEAT FIXED COMMERCIAL RATION WITH FERMENTED DUCKWEED SUBSTITUTION - A. R., Anggraini; Lindawati, S. A.; Budiasa, I K. M. (Jurnal Peternakan Tropika, 2024)
This study aims to determine the organoleptic and physical quality of broiler meat fed commercial rations with substitute fermented Saccharomyses cerevisiae fermented duckweed ( Lemna minor ). The research was conducted from November to December 2022 at UD. Darmasuci Farm, Abiansemal, Badung Regency, Bali and Laboratory of Animal Products Technology, Faculty of Animal Husbandry, Udayana University. In this study, a completely randomized design (CRD) was used with four treatments and four replications. The treatment consisted of: meat from broilers fed 100% commercial ration (P0), fermented duckweed substituted ration 5% (P1), fermented duckweed substituted ration 10% (P2), and fermented duckweed substituted ration 15% (P3). The variables observed were organoleptic quality (color, aroma, taste, tenderness, and overall acceptability) and physical quality (pH, drip loss, cooking loss, and water content). The conclusion from this study are commercial diets substitute with fermented duckweed had an effect on the pH and raw loss, but did not affect the color, aroma, taste, tenderness, overall acceptability, cooking loss and water content of broiler meat. As well as the response of the panelists to the organoleptic quality of broiler meat showed a favorable direction.